Antibacterial Strategies from the Sea: Polymer‐Bound Cl‐Catechols for Prevention of Biofilm Formation. (9th November 2012) - García‐Fernández, Luis; Cui, Jiaxi; Serrano, Cristina; Shafiq, Zahid; Gropeanu, Radu A.; Miguel, Verónica San; Ramos, Jagoba Iturri; Wang, Miao; Auernhammer, Gunther K.; Ritz, Sandra; Golriz, Ali A.; Berger, Rüdiger; et al.
<x xml:space="preserve">Abstract</x> Inspired by the amino acid 2‐chloro‐4, 5‐dihydroxyphenylalanine (Cl‐DOPA), present in the composition of the proteinaceous glue of the sandcastle worm Phragmatopoma californica, a simple strategy is presented to confer antifouling properties to polymer surfaces using (but not releasing) a bioinspired biocide. Cl‐Dopamine is used to functionalize polymer materials and hydrogel films easily, to prevent biofilm formation on them. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>